2015
DOI: 10.1007/s10291-015-0464-2
|View full text |Cite
|
Sign up to set email alerts
|

Tight integration of ambiguity-fixed PPP and INS: model description and initial results

Abstract: The traditional PPP/INS system is still not used as widely as the DGNSS/INS system in precise applications, although no local reference stations are required. The main reason that prevents its use is that the traditional PPP/ INS system is based on the float ambiguity solution, which leads to long convergence period and unstable positioning accuracy. We propose a tightly coupled ambiguity-fixed PPP/INS integration. First, the derivation of the observation model of the ambiguity-fixed PPP at the single-differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…However, the high-accuracy INS is expensive, and the error will accumulate over time [1]. It often relies on external auxiliary information for correction [2,3]. In the early stages of the GPS (Global Positioning System) system construction, some people put forward the idea of using GPS for attitude determination.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high-accuracy INS is expensive, and the error will accumulate over time [1]. It often relies on external auxiliary information for correction [2,3]. In the early stages of the GPS (Global Positioning System) system construction, some people put forward the idea of using GPS for attitude determination.…”
Section: Introductionmentioning
confidence: 99%
“…This method is mostly used in the precise point positioning (PPP)/INS tightly coupled system. The INS information is used to assist in PPP ambiguity resolution, which can effectively improve the speed of re-fixing the ambiguity after losing lock, but the initialization time is still long [27][28][29][30]. To improve the reliability of the RTK algorithm, Dorn et al introduced single-difference ambiguity into the state equation to achieve high-precision positioning results, but it also introduced receiver clock bias and clock drift [31].…”
Section: Introductionmentioning
confidence: 99%
“…Liu realized GPS PPP ambiguity fixed solution and PPP/INS tight coupling model of ambiguity fixed solution by using integer phase clock products and inter satellite single difference model. The results showed that the positioning accuracy could reach centimeter level after ambiguity fixed, the velocity and attitude accuracy were equivalent to DGNSS/INS combination accuracy, and INS could speed up the re-fixed time of PPP under the condition of poor signal [24]. Han improved the PPP/INS tight coupling algorithm by using the prior information constraint of tropospheric delay, and the positioning accuracy was improved to a certain extent [25].…”
Section: Introductionmentioning
confidence: 99%